2022
DOI: 10.1007/s00232-022-00230-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Biological Replication and Evolution Independent of the Central Dogma: Insights from Protein-Free Vesicular Transformations and Protein-Mediated Membrane Remodeling

Abstract: Biological membrane remodeling is central to living systems. In spite of serving as “containers” of whole-living systems and functioning as dynamic compartments within living systems, biological membranes still find a “blue collar” treatment compared to the “white collar” nucleic acids and proteins in biology. This may be attributable to the fact that scientific literature on biological membrane remodeling is only 50 years old compared to ~ 150 years of literature on proteins and a little less than 100 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 280 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…Due to our interest in secreted proteins, we first identified that 630 of these genes were extracellular (see the Materials and Methods section). Of these 630 extracellular genes, 310 correspond to nonmembrane (i.e., may be assumed to be soluble proteins that were secreted) and 320 correspond to membrane proteins (i.e., may be assumed to be extracellular membrane proteins including those associated with secreted vesicles) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to our interest in secreted proteins, we first identified that 630 of these genes were extracellular (see the Materials and Methods section). Of these 630 extracellular genes, 310 correspond to nonmembrane (i.e., may be assumed to be soluble proteins that were secreted) and 320 correspond to membrane proteins (i.e., may be assumed to be extracellular membrane proteins including those associated with secreted vesicles) …”
Section: Resultsmentioning
confidence: 99%
“…The science of biology, however, is yet to benefit from the general acceptance of even a single universally applicable tenet despite some recent discoveries. Arguably, the only consensus definition in biological sciences is that of a cell as a unit of life. Even the unparalleled discovery of the central dogma, earlier believed to be universal, does not apply to certain aspects of biological replication . On the one hand, a case-by-case assessment of phenomena renders biological sciences relatively empirical.…”
Section: Conclusion: Is There a Law Of Conservation Of Secreted Prote...mentioning
confidence: 99%
See 2 more Smart Citations
“…In general, it is thought that vesicular assemblies, mimicking biological cells and subcellular compartments, are formed due to the hydrophobically-driven self-assembly of amphiphilic molecules in aqueous environments. 22,[37][38][39][40] At the same time, manifestations of biological functions result from the action of polymeric structures ( predominantly proteins) within particular ranges of environmental variables. 41,42 Vesicular assemblies utilize the full spectrum of four weak interactions (hydrogen-bonding, ionic interactions, van der Waals forces and hydrophobic interactions).…”
Section: Discussionmentioning
confidence: 99%